A Review on Structural Performance of Fly Ash Reinforced Concrete Beam - Solahuddin, Azuwa (IJISET, 2021)
A reinforced concrete beam is primarily made up of cement, sand, aggregate, reinforcing bar and water. Fly ash is a material used in strengthening reinforced concrete beam to enhance the structural strength and ductility. This paper presents the experimental study results on the structural performance of fly ash reinforced concrete beam. This article addresses the experimental parameters of reinforced concrete beams containing fly ash with different percentages. Therefore, experimental investigations were carried out to find the structural performance of the reinforced concrete beam containing fly ash. The results are also compared with reinforced concrete beam without fly ash content. The performance data results are compared with each other. It is observed that fly ash improves the structural performance of the reinforced concrete beam. This study indicates that fly ash will benefit by using it as additional material in reinforced concrete beam production.